TWIN MUMMIFICATION IN NON-DESCRIPT DOE: A CASE REPORT - Sasidharan, Jisna Kuttiyeri; Gupta, Shashikant; Pradeep,; Chandra, Pradeep; Kumar, Brijesh; Ghosh, Subrata Kumar (The Indian Journal of Animal Reproduction, 2023)
A non-descript doe in its second parity was presented with the history of thick brownish-red vaginal discharge.  The detailed gynecological examination of the doe revealed an engaged dead fetus in the birth canal. Gentle traction was applied using small blunt eye hook following adequate lubrication of the birth canal and two mummified fetuses were delivered one after another. Adequate treatment ensured uneventful recovery of doe without any complications.
Keywords: Doe; Mummified fetus; Haematic mummification